DESIGN AND CONSTRUCTION STUDY OF MOLLEN DRYER TYPE - Sutrisno , Asep Dedy (Sean Institute, 2023)
The aim of this research for mollen dryer project is to give application to small and middle industries in dry juice production. Benefit from this research was to give more choice for dryer utilize, with used dried air as heating media. The principal of this mollen dryer was based on hot air blows into mollen tube, rotation of mollen tube and move of agitator in mollen tube to material mixing was to spreading of heated air over to entire heating material and water evaporating to get good dried products criterion. The steps of this studied as followed : literature studied, basic designing, detail engineering design (DED), revision of DED, design simulation, prepared of construction material, construction of mollen dryer, and test of operational to dried products. The result from drying tested of mollen dryer which had desgned and constructed, with air flow between 1.1 m/s - 4.5 m/s during operating about 4 - 5 hours, we got pineapple powder equal to 550 g, water content equal to 2.71 %, and the content of vitamin C about 16.13 mg / 100 g, from pineapple fruit extracts with total dissolved solid equal to 16 obrix which have been enhanced by sugar equal to 1100 g with water content equal to 82.3 %. Totally operational of mollen dryer have been designed and construction was efficient, effective, and good.